Aneurysm Clipping after Partial Endovascular Embolization for Ruptured Cerebral Aneurysms - Nomura, M. (Centauro S.r.l., 2000)
The aim of this study was to investigate the advantages and disadvantages of a two-stage treatment for ruptured cerebral aneurysms; partial embolization in acute stage followed by clipping in chronic stage of subarachnoid hemorrhage. Between April 1997 and August 1999, twenty ruptured cerebral aneurysms were initially treated endovasculary using Guglielmi detachable coils in our institution. Among them, complete embolization could not be achieved in 6 lesions. For these lesions, subsequent clipping was added. The radiological and operative findings, and outcomes of these cases were retrospectively reviewed. In 1 case, rerupture occurred during the endovascular procedure. Rerupture was not observed in any cases in the postembolization period. In 2 cases, complications related to the clipping but not the endovascular procedure occurred. These complications included impaired visual acuity for unverified reasons, and memory disturbance due to sacrifice of a perforator arising from the anterior communicating artery. In 3 cases, coil extraction was needed during the clipping, because the loops of the coil extended into the residual neck. Complications related to coil extraction were not observed in these 3 cases. Acute partial embolization of ruptured aneurysm appears to be effective for the prevention of subsequent rerupture during the subacute period, in which treatment for vasospasm should be performed, and the clipping procedure. However, in the case of relatively large aneurysms, small arteries or other normal structures behind the aneurysm cannot be observed directly during surgery, because of the immovability of the embolized aneurysm. Further; complete clip closure is impossible when loops of coil herniate into the neck. In such situations, coil extraction with or without resection of the aneurysm might be necessary, and care must be taken not to damage parent artery and surrounding vessels.